The Influence of Information and Communication Technology on the Natyashastra: A Digital Age Perspective - K. Itagi, Sathish; Yeasmin, Rubina (Bodhi: An Interdisciplinary Journal, 2024)
The Natyashastra is a dramatic art form that includes a variety of elements like music, dance, dialogue, costume, tune, body language, and many more. It was envisioned by Bharata Muni, an ancient Sanskrit poet. The eight rasas are incorporated and have influenced contemporary art forms with integral cultural values. In the digital age, the Natyashastra finds itself in competition with a more communicative and popular mass culture, which includes a variety of new media tools like TV, radio, video, films, OTT platforms, and teleserials. These platforms not only entertain but also provide energetic infotainment by leveraging digital platforms to share experiences. The Natyashastra has influenced changes in audience attitudes and behaviors and enhances affirmative action, performance styles, and artistic amusement. It preserves the history, culture, traditions, and values of heritage in this digital era. Many theatre groups continue to keep dramatic culture alive in this satellite age. Today, all types of actors and audiences depend on various communicative tools to watch and perform the Natyashastra. Multimedia devices like laptops, tablets, smartphones, personal computers, digital cameras, tripods, video projectors, multiple software applications, social media, and more are now used to host live performances directly via several interactive platforms. SEO and other search engines are engaging with both digital and analog technologies.